2018
DOI: 10.1590/1982-021620182038817
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors in infants participating in a Follow-up program

Abstract: Purpose: to identify the main health risk factors of infants participating in a follow-up program. Methods: a longitudinal prospective study conducted with 540 high-risk infants observed in the follow-up clinic of the Hospital Materno Infantil in Goiânia in the State of Goiás, Brazil. All biological data of the infants from birth, prenatal, and postnatal periods were collected through assessment sessions with their mothers and medical chart reviews. Data were analyzed through binary logistic regression to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
8
0
10
Order By: Relevance
“…Formiga, Silva and Linhares' study 12 reinforce the need of the multidisciplinary team for the all-encompassing care of children and their families, especially those whose development are perceived as being at risk.…”
Section: Introductionmentioning
confidence: 84%
“…Formiga, Silva and Linhares' study 12 reinforce the need of the multidisciplinary team for the all-encompassing care of children and their families, especially those whose development are perceived as being at risk.…”
Section: Introductionmentioning
confidence: 84%
“…Deve-se levar em consideração obviamente que as gestações que duram menos, as gestantes fazem menos consultas de pré-natal. Ainda assim, a baixa adesão ao pré-natal vai de acordo com Formiga et al [18] em que a média de consultas pré-natal de 540 bebês de risco foi de 5,47. Conforme Mucha et al [19], RNs com menos de seis consultas no pré-natal tiveram 1,3 vezes maior risco de internação.…”
Section: Discussionunclassified
“…These findings converge with results from the national and international literature, in which analysis conducted in Turkey found that GA less than 37 weeks of gestation and birth weight less than 2,500 g were among the most important variables related to long periods of hospitalization of NB (14) . In a Brazilian study, prematurity, low birth weight and the need for ICU admission were highlighted among biological risks (15) .…”
Section: Discussionmentioning
confidence: 99%